WADY WRODZONEAnomalous low insertion of superior vena cava into right atrium in infant with partial anomalous drainage of left pulmonary veins - Karolczak, Maciej A.; Mądry, Wojciech; Grabowski, Krzysztof; Tarnowska, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Anomalies of the localization of the upper cavoatrial junction are extremely rare. We present the case of 9 months old boy with low insertion of superior vena cava to right atrium and coexistent partial anomalous drainage of left pulmonary veins.